Laser-induced breakdown spectroscopy (LIBS) for printing ink analysis coupled with principle component analysis (PCA) - Hui Y.W.; Mahat N.A.; Ismail D.; Ibrahim R.K.R. (American Institute of Physics Inc., 2024)
Indexed by Scopus